ТЕОРЕТИКО-МЕТОДОЛОГИЧЕСКИЕ АСПЕКТЫ ГЛОБАЛИЗАЦИИ: ИЗУЧЕННОСТЬ, СОСТОЯНИЕ, ПЕРСПЕКТИВЫ (Journal of Economic Research & Business Administration, 2015)
In the article considers the modern theory of the development of community and their forms of behavior in different countries of the world. It has given the opinions of well-known scientists-sociologists, scientists of politology, economists on the achievement of phenomena of globalization and theoretical aspects of globalization. The author paid attention to the readers on basic scenes of globalization, particularly one of them is globalization.